Women, sexual violence and the Indonesian killings of 1965-66 - Pohlman, Annie., author.
1 online resource (xiii, 188 pages)
Keywords: "The Indonesian massacres of 1965-1966 claimed the lives of an estimated half a million men, women and children. Histories of this period of mass violence in Indonesia's past have focused almost exclusively on top-level political and military actors, their roles in the violence, and their movements and mobilization of perpetrators. Based on extensive interviews with women survivors of the massacres and detention camps, this book provides the first in-depth analysis of sexualised forms of violence perpetrated against women and girl victims during this period"--